FINDING THE CRAMPED SPACE IN A CITY: THE ACCESSIBILITY ASSESSMENT OF PONTIANAK CITY BASED ON THE GRIDDED POPULATION DENSITY - Bontor Jumaylinda Br Gultom; Affrilyno Affrilyno; Dian Rahayu Jati; Andi Andi (Diponegoro University, 2022)
Recently, the data on population distribution only illustrates a number of density of a city or a district. Thus, it can not show the exact area of the crowded population. The population density in a city can cause a mismatch between the available space and the carrying capacity of its environment. The discrepancy can make it challenging to allocate resources or assistance in a disaster. In this regard, it is necessary to conduct research on the population's spatial distribution and the potential for movement between spatial segments. It is important to locate the cramped space where the space has high density but low accessibility in the city. This study aimed to determine the distribution of the population in the grid of 0.5 km and its assessment on accessibility in Pontianak City. The methodology used in this research is the population mapping method and space syntax. This research performs a quadrant mapping and correlation analysis to assess city accessibility. The result of the population distribution of Pontianak City shows the density concentrated in the city's center and dispersed from the river to inland. The quadrant maps show that Pontianak City has good accessibility. The quadrant map can be used as a recommendation for city development. With the quadrant division, the government can first concentrate its resources on repairing or developing the grid unit with low accessibility. With a coefficient correlation of 40.5 % and 50.9 %, this research found a positive and moderate correlation between density distribution and accessibility.